PENGARUH PENGGUNAAN APLIKASI DILETA TERHADAP PENGUATAN NILAI INTEGRITAS ANAK USIA DINI - Popi Dayurni; Kurniati Rahmadani (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of using the DILETA application on strengthening the integrity values ​​of early childhood. The background of the study lies in previous findings that show that although the DILETA application is effective in improving several aspects of character, integrity values ​​are still the component with the lowest achievement. This study uses a quantitative approach with an explanatory design through simple linear regression analysis. The study sample consisted of 30 children aged 5–6 years who participated in learning using the DILETA application. The research instruments were an application usage questionnaire and an integrity observation sheet that had been validated by experts. The results showed that the use of the DILETA application had a significant effect on children's integrity values ​​(p < 0.05), with a regression coefficient of 0.599. The determination value (R² = 0.457) indicates that 45.7% of the variation in children's integrity is explained by the use of the application, while the rest is influenced by external factors such as habits at home, the school environment, and children's social interactions. These findings confirm the effectiveness of ethical dilemma simulations in stimulating moral development according to the theories of Piaget, Kohlberg, and Hurlock. However, the initial version of the DILETA application was still linear and therefore unable to provide an adaptive moral experience.